UNBIASED PATH TRACING OPTIMIZATION USING PARALLELISM, ADAPTIVE SAMPLING, AND RECONSTRUCTION - Rifqi Rahman, Raden
A major challenge in 3D rendering using the path tracing algorithm is achieving a high quality image with a low amount of noise in a reasonable amount of time. Therefore, it is necessary to incorporate optimization techniques to improve path tracing performance in terms of rendering time and image quality. Recent advances in path tracing optimization introduce optimization techniques that are capable of rendering a high quality image in a short time. However, such techniques often introduce a slight bias, which may divert the resulting image from the ground truth. Hence, unbiased path tracing optimization to boost rendering speed and image quality is yet to be explored.